LABOR MOBILITY, INFORMALITY AND WAGE INEQUALITY IN BRAZIL - M. Ruesga, Santos; da Silva Bichara, Julimar; Monsueto, Sandro E. (Investigación Económica, 2015)
Occupational mobility and its impacts on urban Brazilian workers’ wages are analyzed in this paper. Data show high labor mobility in Brazil, especially among workers in the informal sector. The greater mobility of informal workers does not necessarily imply better wage trajectories and, further, workers’ mobility is restricted by labor market segmentation. Differences in upward job movements mean that informal labor receives low wages for longer periods over a working life, leading to important consequences for income differentials in Brazil.